Somatic integration of single ion channel responses of α7 nicotinic acetylcholine receptors enhanced by PNU-120596. - Victor V Uteshev (PLoS ONE, 2012)
Positive allosteric modulators of highly Ca(2+)-permeable α7 nicotinic acetylcholine receptors, such as PNU-120596, may become useful therapeutic tools supporting neuronal survival and function. However, despite promising results, the initial optimism has been tempered by the concerns for cytotoxicity. The same concentration of a given nicotinic agent can be neuroprotective, ineffective or neurotoxic due to differences in the expression of α7 receptors and susceptibility to Ca(2+) influx among various subtypes of neurons. Resolution of these concerns may require an ability to reliably detect, evaluate and optimize the extent of α7 somatic ionic influx, a key determinant of the likelihood of neuronal survival and function. In the presence of PNU-120596 and physiological choline (~10 µM), the activity of individual α7 channels can be detected in whole-cell recordings as step-like current/voltage deviations. However, the extent of α7 somatic influx remains elusive because the activity of individual α7 channels may not be integrated across the entire soma, instead affecting only specific subdomains located in the channel vicinity. Such a compartmentalization may obstruct detection and integration of α7 currents, causing an underestimation of α7 activity. By contrast, if step-like α7 currents are integrated across the soma, then a reliable quantification of α7 influx in whole-cell recordings is possible and could provide a rational basis for optimization of conditions that support survival of α7-expressing neurons. This approach can be used to directly correlate α7 single-channel activity to neuronal function. In this study, somatic dual-patch recordings were conducted using large hypothalamic and hippocampal neurons in acute coronal rat brain slices. The results demonstrate that the membrane electrotonic properties do not impede somatic signaling, allowing reliable estimates of somatic ionic and Ca(2+) influx through α7 channels, while the somatic space-clamp error is minimal (~0.01 mV/µm). These research efforts could benefit optimization of potential α7-PAM-based therapies.